A green approach toward antibody purification: a sustainable biomimetic ligand for direct immobilization on (bio)polymeric supports. Issue 12 (11th November 2013) - Barroso, Telma; Lourenço, Anita; Araújo, Marco; Bonifácio, Vasco D. B.; Roque, Ana C. A.; Aguiar‐Ricardo, Ana
<x xml:space="preserve">Abstract</x> This paper presents a sustainable strategy for improving the capture of antibodies by affinity chromatography. A novel biomimetic ligand (4‐((4‐chloro‐6‐(3‐hydroxyphenoxy)‐1, 3, 5‐triazin‐2‐yl)oxy)naphthalen‐1‐ol) (TPN‐BM) was synthesized using a greener and simple protocol to overcome solubility limitations associated with ligand 22/8, known as artificial protein A. Furthermore, its subsequent immobilization on chitosan‐based monoliths induced by plasma surface activation allowed the design of a fast and efficient chromatographic platform for immunoglobulin G (IgG) purification. The TPN‐BM functionalized monoliths exhibited high‐binding capacity (160 ± 10 mg IgG per gram of support), and a selective capture of monoclonal antibodies directly from mammalian crude extracts in 85 ± 5% yield and 98% of purity. The synthesis of ligand TPN‐BM and the routes followed for monoliths preparation and functionalization were inspired in the green chemistry principles allowing the reduction of processing time, solvents and purification steps involved, turning the integrated system attractive from an economical and chemical point of view. Copyright © 2013 John Wiley & Sons, Ltd.